A comparison of diet of two species of anchovies Encrasicholina punctifer (Fowler, 1938) and Encrasicholina heteroloba (Nelson, 1983) in Ayungon, Negros Oriental. - Eliarda, Melissa R. (2019.)
The diet composition of the two occurring species of anchovies, Encrasicholina Encrasicholina heteroloba and Encrasicholina punctifer in Anibong, Ayungon, Negros Oriental have been studied through gut content analysis. The guts were removed, weighed, and opened and the non-chyme components were taken out and identified and classified into the lowest taxonomical groups. The empty gut sacs were also weighed. The percentage of chime and non-chyme components of each gut was measured. Results show that more than 70% of the gut contents of the two species of Encrasicholina were chime and the remaining percentage were non-chyme. The most abundant prey types found in Encrasicholina heteroloba were cyclopoids (33.19%), unidentified copepod heads (19.36%) bivalve veligers (13.35%), unidentified eggs (7.66%) and gastropod veligers (7.35%). In Encrasicholina punctifer, the most abundant prey types were unidentified copepod heads (27.74%), unidentified eggs (21.43%), microplastics (13.76%), cyclopoids (13.67%), and fish eggs (8.98%). These results show that both Encrasicholina heteroloba and Encrasicholina punctifer prefer small copepads. The changes in the dietary composition of each species of Encrasicholina with the increase in body size would spread the food resources both between species and among the individuals of each species thus reducing the potential for interspecific and intraspecific completion of food resources in the fish community.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Anchovies -- Ayungon, Negros Oriental; Encrasicholina punctifer; Encrasicholina heteroloba